A narrative review on the relationship between consumption of sugar-sweetened beverages and post-partum non-communicable diseases among women - Malik, Zoha Imtiaz; Shah, Syed Hassan Bin Usman; Zafar, Saira; Farooq, Umar; Abid, Juweria; Ahmad, Abdul Momin Rizwan (Frontiers in Public Health, 2025)
Recent years have seen an increased trend in the consumption of sugar-sweetened beverages (SSBs), which have been associated with weight gain and retention. These effects are also observed in women of reproductive ages, especially during the post-partum period, which enhances their risk of developing several non-communicable diseases later in life. The current narrative review aims to explore the relationship between SSBs consumption and post-partum weight gain and retention, by evaluating results garnered from observational and interventional studies, and reviews done previously on this topic. Literature search on Google Scholar and PubMed using the appropriate key words identified 8,653 articles, which after adjustment for timeline (2017–2025), and title, abstract and text screening for eligibility, resulted in 32 articles being selected. Evidence from the included articles suggests that SSBs result in weight gain due to their high caloric content, role in metabolic dysregulation and hormonal disruptions, exacerbating poor dietary intake and, increased blood glucose levels which ultimately lead to higher adiposity, both of which are risk factors for chronic diseases. Recommended solutions to reduce SSB intake in all population groups, particularly reproductive age women, include educational campaigns, SSB awareness using media, regulating SSBs sales through taxes and access policies, and making safe water available for the public. This review highlights the need to further delve into SSBs’ impacts on health and to focus on developing strategies to reduce their access and availability on a mass level. Barriers toward effective implementation of SSB regulation strategies also need to be addressed for more efficient and effective results.